Potential of Papaya Seed (Carica Papaya L) Biosorbent for Textile Dyes Absorption - Indriani, Dini; Agustine, Liana; Nurani, Lisna Wahyu; Khofifah, Tsani; Surakusumah, Wahyu; Dewina, Restu Utari (-, 2025)
Biosorbents are biological materials used to remove pollutants from solutions passively. Papaya seeds are believed to be a biosorbent candidate because they contain SiO2, which has the potential to act as an adsorbent. Papaya seed adsorbent was made by adding H2SO4 as an activator and using Wantex red as the tested dye. This research aims to determine the potential concentration of papaya seeds as a biosorbent. The analysis used is qualitative, quantitative, and a significance test analysis. The method in this research uses 0.5 g (1%); 1.5g (3%); 2.5g (5%); 3.5 g (7%) of papaya seed biosorbent dissolved in Wantex red dye solution and analyzed using a UV-Vis spectrophotometer. The qualitative color results show contrasting color differences where the most transparent color is the dye added with 1.5 g and 2.5 papaya seed biosorbent, and the UV-Vis spectrophotometer absorbance results show that the best biosorbent mass is 1.5 g and 2.5 g with the highest absorbance power, namely 0.024 mg/g and 0.009 mg/g.